Implementation of Fuzzy Sets in the Non-Isothermal Pyrolysis of Biomass - Dhaundiyal, Alok; Singh, Suraj B. (JNRD - Journal of Natural Resources and Development, 2017)
This paper proposes the study of the application of fuzzy logic on the relevant parameter of biomass pyrolysis. The frequency factor, the upper limit of ‘dE’, and the scale and shape parameters of the fuzzy Gamma distribution were fuzzified in order to estimate randomness and to accommodate realistic values. The distribution function, f (E), of the activation energies was assumed to follow the fuzzy Gamma distribution. Thermo-analytical data was found experimentally with the help of TGA/DTG analysis. The approximated solution of the DAEM was obtained using the asymptotic approach.